Adopting Review, Reflect and Re-focus [Triple R] sessions to support pre-registration therapeutic radiography students post clinical placement. Issue 4 (November 2021) - Stewart-Lord, A.; Walker, C.; Williams, R.
Abstract: Introduction: Education and training strategies in Therapeutic Radiography are challenged in recruiting and retaining students in the profession. Clinical oncology centres are often viewed as stressful environments for students due to rapid advances in technology and reported bullying and harassment. Educators continue to work with clinical partners in developing strategies to promote resilience and reduce negative attitudes. The overall aim of this project was to explore the use of Triple R sessions as a new method of student reflection. Methods: The Review, Reflect and Re-focus (Triple R) sessions were designed to enable students to learn from their clinical experiences and; apply their understanding and positivity when they return to clinical placement. Eleven sessions were completed across 7 student cohorts in one academic year. Qualitative data was collected from feedback forms, as well as academic field notes, and analysed thematically. Results: Two main themes focused on: (1) staff interactions and (2) student expectations. Results showed that Triple R sessions were helpful in drawing out the experiences of students in a positive way to reflect on their own development. The sessions enabled critical self-analysis and improved problem-solving skills, particularly evident during peer discussions. Conclusion: Triple R sessions explored the influence of a positive approach on students' perceptions of their overall placement. Evaluation of the data indicated that, following academic and peer discussion, students' perceptions tended to be a more positive overall view of their placement. Implications for practice: Triple R sessions can be used in academic and clinical environments to enable positive student interactions.